2011
DOI: 10.2174/156802611796117586
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells with Neurogenic Potential and Steroid Hormones

Abstract: Pluripotent and multipotent stem cells with differentiation potential to neural phenotypes have been described and characterized in the last decades. Embryonic stem cells, as well as neural stem cells from developing and adult nervous system, can differentiate into different types of neurons, astrocytes or oligodendrocytes. Although the initially identified actions of estradiol, progesterone and testosterone are related to sexual reproductive functions, recent evidence shows that these steroid hormones modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 102 publications
(136 reference statements)
0
4
0
Order By: Relevance
“…Glycoproteins and steroid hormones have been reported to regulate different aspects of neurodevelopment and neural stem cell properties, where they usually play neurotrophic roles. 79 , 80 , 81 We found that the FSH pathway was activated by ING5, with ING5 overexpression increasing levels of membrane bound FSH receptors. Blocking the FSH pathway also reduced the ability of BTICs to self-renew.…”
Section: Discussionmentioning
confidence: 79%
“…Glycoproteins and steroid hormones have been reported to regulate different aspects of neurodevelopment and neural stem cell properties, where they usually play neurotrophic roles. 79 , 80 , 81 We found that the FSH pathway was activated by ING5, with ING5 overexpression increasing levels of membrane bound FSH receptors. Blocking the FSH pathway also reduced the ability of BTICs to self-renew.…”
Section: Discussionmentioning
confidence: 79%
“…Stem cells with multi differentiation potential for neuronal phenotypes are influenced by steroid hormones, such as regulating gene expression by binding to intracellular steroid receptors, activation of intracellular pathways involving kinases or intracellular calcium signaling, and modulation of receptors for neurotransmitters (reviewed in Velasco, 2011). Interestingly, steroid hormones can even substitute for modulate the action of growth factors and also directly influence self-renewal, proliferation, differentiation, or cell death of neurogenic stem cells.…”
Section: Neurosteroids and Neurosteroidogenic Antidepressants Regulatmentioning
confidence: 99%
“…Sex steroid hormones participate in many physiological processes, including proliferation of neural precursors, neuronal differentiation or neuroprotection (8–10). Undifferentiated mouse ES cells express progesterone receptor (PR) isoforms A and B, as well as estrogen receptor (ER)‐α and ER‐β (11, 12).…”
Section: Introductionmentioning
confidence: 99%